A user study of the family history center at the church of Jesus Christ of latter-day saints Manila Philippines administration office - Quiñones, Klarenz Kristoffer M.; Olgado, Benedict S. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
Archives aim to preserve documents for easy access of the users. Satisfying the information needs of a user is a top priority of archives. In this light, an archives user study was conducted at the Family History Center (FHC) of The Church of Jesus Christ of Latter-Day Saints (LDS) Manila Philippines Administration Office. This study aims to profile FHC users and evaluate the FHC archives in terms of service product and process, service environment, service workers, and other yardsticks to improve and develop the archives to better serve FHC users. Data gathering for this research was done through an online survey of FHC users and through a semi-structured interview with the FHC's Manila Administration Office Director
The LDS Church is a family-centered religion whose core doctrine is the concept of a united family that lives and progresses forever. The family is eternally bound to each other and will remain as such even after death through a process called "sealing" which can also include deceased ancestors. Thus, a basic requirement for every Mormon is to research and construct his/her family tree. To facilitate this, the LDS Church built a global database of facsimile copies of pertinent records. Prior to computerization, the records were preserved in microfilms. Today, this digital database can be accessed, free of charge, through the Internet using one's own computer or through the facilities of the Family History Center, an office built by the LDS Church specifically for family history research
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Church of Jesus Christ of Latter-Day Saints -- Philippines; Families -- History